Why does she suffer prolonged status asthmaticus? - Mora Claramita; Nur Afrainin Syah (Review of Primary Care Practice and Education (Kajian Praktik dan Pendidikan Layanan Primer), 2019)
A mother (Y) aged 55 years, was hospitalized with ‘Status Asthmaticus’, for 4 days in a hospital, with admission through an Emergency Department Service. The case history was ‘Intermittent Asthma’ with corticosteroid inhaler treatment for the past three years and ‘Diabetes Mellitus’ (DM) Type 2, controlled by the treatment of Metformin and Acarbose. The results of the history, physical examination, and laboratory lead to the main diagnosis ‘Status Asthmaticus’. Blood glucose before and when at the hospital was within normal limits (with treatment). Asthma attack was absent during the last 2 years, relapsed 2 years ago because of 'Bronchopneumonia'.